Perinatal mortality in breech deliveries at Dr. Said%ito General Hospital, Yogyakarta - Sulchan Sofoewan Sulchan Sofoewan (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1997)
Breech delivery is still of importance to discuss, because perinatal morbidity and mortility are higher than those vertex deliveries. A retrospective study was carried out on 141 cases of breech deliveries in Dr. Sardjito General Hospital during 1989 - 1990. The highest perinatal mortality was due to low birth weight: 17 cases (12%) compared to all cases (4.2%). No perinatal mortality of multiparity cases was found compared with cases of nulliparity i.e. 13 cases (17.0%). The type of breech presentation were frank breech: 85 cases (60.3%); incomplete: 21 cases (14.9%) and complete: 35 cases (24.8%). The highest perinatal mortality was frank breech presentation: 15 cases (17.6%). According to the termination of delivery, breech extraction has the highest perinatal mortality (23.%).Key Words: breech presentation - parity - perinatal - morbidity - mortality